PENGEMBANGAN MEDIA KOMIK DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SD - Danang Pamungkas; Wahyudi Wahyudi; Endang Indarini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research and development aims to develop and test the validity, practicality, and effectiveness of comic-based modules in mathematics in elementary schools. The research method used is R&D with the ADDIE development model which consists of five stages, namely 1) analysis, 2) design, 3) development, 4) implementation and 5) evaluation ). Product validity was obtained from expert testing with expert validation instruments. The practicality of the product in the form of comic media was obtained through limited trials with a questionnaire instrument. The effectiveness is obtained through one class trial with one group pretest-posttest design then the results are tested using Paired SamplesvT Test. The result of this research is that the comic-based media module generally improves the ability to solve mathematical problems in the classroom material of five elementary school students. Learning media are declared valid based on the test of media experts, material experts and learning experts. Learning media are declared practical based on the results of the questionnaire responses of teachers and students. Learning media are declared effective based on the results of students' Paired SamplesvT Test pretest-posttest.